2009
DOI: 10.1111/j.1525-1446.2009.00817.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Assessment of the Brazilian Version of the Breastfeeding Self‐Efficacy Scale

Abstract: Altogether, our findings suggest that BSES translated into Portuguese may be a reliable and valid measure to assess maternal BSE in Brazilian culture. Minor changes may be needed to use it in other Portuguese-speaking countries, such as Portugal and Mozambique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 26 publications
(46 reference statements)
1
30
0
7
Order By: Relevance
“…Thus, it is observed that the adolescents had high levels of confidence to carry out the practice of breastfeeding. Other studies in the state of Ceará that have evaluated the self-efficacy of in women to breast-feed, with no specific age, has also shown that they have high self-efficacy [12,28]. Therefore, it is evident that women from Ceará that are assisted in public systems have confidence in the practice of breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it is observed that the adolescents had high levels of confidence to carry out the practice of breastfeeding. Other studies in the state of Ceará that have evaluated the self-efficacy of in women to breast-feed, with no specific age, has also shown that they have high self-efficacy [12,28]. Therefore, it is evident that women from Ceará that are assisted in public systems have confidence in the practice of breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we used the internal consistency measured by Cronbach's Alpha (α) as indicative of reliability [12].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cronbach's alpha coefficient was .96, and support for predictive validity was demonstrated through positive correlations between BSES scores and infant-feeding practices at 6 weeks postpartum [10] . The translation to Portuguese and psychometric assessment of the full BSES, which was coordinated by a Brazilian nurse research team in the northeast Brazil, is presented elsewhere [11,12] .…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Its analysis permits identifying the women at greater risk for early weaning and making individual interventions when necessary. 20 Studies that analyzed this variable among adult mothers identified that, the greater the woman's trust, the greater the chance of maintaining breastfeeding longer. [21][22] Nevertheless, the trust to breastfeed among adolescent mothers has been hardly explored, although some studies have iden-tified that the young maternal age is one of the characteristics of the women who wean early.…”
Section: Introductionmentioning
confidence: 99%